Enhancing Energy Efficiency Utilized IoT: Power Optimization and Energy Harvesting Techniques for Sustainable and Resilient Systems - Dhafer Yaseen; Hasan Qays; Hasnaa Abdulkareem; Falah Ahmed (مجلة التربية والعلم)
The widespread growth of Internet of Things (IoT) devices, in industries has led to a rise in energy requirements underscoring the importance of sustainable power management solutions. This study talks about the methods for optimizing power usage and harnessing energy to improve efficiency within networks shown in 2 and 2.1. By combining dynamic power management strategies with energy harvesting from sources like thermal and vibrational energies this research explores the potential for creating durable and eco-friendly IoT systems. Through a combination of simulations and real world experiments, We assess the efficacy of these approaches. The results demonstrate that customized power management algorithms paired with context energy harvesting can significantly lower the energy consumption of devices without compromising their performance levels. This investigation enhances our knowledge of networking by suggesting a framework for implementing energy efficient practices in IoT by thermal and vibrational energies infrastructures paving the way, for more eco friendly technological environments. This study does not confirm the viability of self sustaining networks but also suggests future research paths to further enhance energy efficiency and resilience in IoT setups or systems.